The Real Winner's Curse (2020)
Traditional theories of democracy suggest that political representation of excluded groups can reduce their incentives to engage in conflict and lead to lower violence. However, this argument ignores the response of established elites when (1) their interests are threatened by the policy stance of new political actors and (2) elites have a comparative advantage in the exercise of violence. Using a regression discontinuity approach, we show that the narrow election of previously excluded left-wing parties to local executive office in Colombia results in a one standard deviation increase in violent events by right-wing paramilitaries. We interpret this surge in violence as a reaction of traditional elites to offset the increase in outsiders' access to formal political power. Consistent with this interpretation, we find that violence by left-wing guerrillas and other actors is unaffected and that violence is not influenced by the victory of right-wing or other new parties in close elections. © 2020, Midwest Political Science Association